STATUS HIGIENIS PADA IBU PENDERITA HIPERTESI DI PUSKESMAS SUKARAME KOTA BANDAR LAMPUNG - Desi Andriyani; Lies Elina; Erni Gultom; Yenny Liesbeth Siahaan (Poltekkes Kemenkes Medan, 2026)
Hypertension is one of the non-communicable diseases with a high prevalence in Indonesia, including in the working area of the Sukarame Health Center, Bandar Lampung. People with hypertension are at risk of oral health problems, especially due to the side effects of medications and a lack of attention to dental and oral hygiene. According to World Health Organization (WHO) data, more than 1 billion people in the world suffer from hypertension, and this number continues to increase every year. In Indonesia, based on Riskesdas 2018, the prevalence of hypertension in the population over 18 years old reached 34.1%. The city of Bandar Lampung as the capital of Lampung Province is also inseparable from the high number of hypertension cases, including in the working area of the Sukarame Health Center. Objective: This study aims to determine the oral hygiene status of women with hypertension who are treated at the Sukarame Health Center. Method: This study used a descriptive design conducted by consecutive sampling carried out on mothers with hypertension who visited the Sukarame Health Center and met the criteria, cross sectional approach, so that a sample of 35 mothers with hypertension was obtained. Data were collected through a clinical examination of oral hygiene using the Oral Hygiene Index-Simplified (OHI-S) index and periodontal tissue condition (CPITN). Research Results : Dental hygiene or OHIS Mothers with Hypertension at the Sukarame Health Center in Bandar Lampung. It was found that 18 respondents (51%) had bad criteria and the health of periodontal tissue CPITN was obtained with shallow pocket criteria for 21 respondents (60%) out of 35 respondents. Conclusion: There is a relationship between oral hygiene status in women with hypertension at the Sukarame Health Center in Bandar Lampung.